Complement 3a receptor in dorsal horn microglia mediates pronociceptive neuropeptide signaling. Issue 12 (29th August 2017) - Doolen, Suzanne; Cook, Jennifer; Riedl, Maureen; Kitto, Kelley; Kohsaka, Shinichi; Honda, Christopher N.; Fairbanks, Carolyn A.; Taylor, Bradley K.; Vulchanova, Lucy
Abstract: The complement 3a receptor (C3aR1) participates in microglial signaling under pathological conditions and was recently shown to be activated by the neuropeptide TLQP‐21. We previously demonstrated that TLQP‐21 elicits hyperalgesia and contributes to nerve injury‐induced hypersensitivity through an unknown mechanism in the spinal cord. Here we determined that this mechanism requires C3aR1 and that microglia are the cellular target for TLQP‐21. We propose a novel neuroimmune signaling pathway involving TLQP‐21‐induced activation of microglial C3aR1 that then contributes to spinal neuroplasticity and neuropathic pain. This unique dual‐ligand activation of C3aR1 by a neuropeptide (TLQP‐21) and an immune mediator (C3a) represents a potential broad‐spectrum mechanism throughout the CNS for integration of neuroimmune crosstalk at the molecular level. Main Points: Spinal C3aR1 expression is localized in microglia and increases after nerve injury. C3aR1 mediates TLQP‐21‐evoked thermal hyperalgesia and contributes to nerve injury‐induced hypersensitivity. TLQP‐21 elicits C3aR1‐dependent Ca 2+ signaling in dorsal horn microglia that increases with neuropathic injury.